2016
DOI: 10.7717/peerj.2691
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing infection and transmission ofAnopheles gambiaedensovirus (AgDNV) in mosquitoes

Abstract: Anopheles gambiae densovirus (AgDNV) is a potential microbial agent for paratransgenesis and gene transduction in An. gambiae, the major vector of human malaria in sub-Saharan Africa. Understanding the interaction between AgDNV and An. gambiae is critical for using AgDNV in a basic and applied manner for Anopheles gene manipulation. Here, we tested the effects of mosquito age, sex, blood feeding status, and potential for horizontal transmission using an enhanced green fluorescent protein (EGFP) reporter AgDNV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…In general, prevalent members of the natural virome should evolve towards lower pathogenicity in their habitual host lineages. Consistent with that expectation, a symbiotic Anopheles densovirus (studied for its potential use as a paratransgenesis tool) elicited low transcriptional response upon infection, and neither mosquito age at infection nor feeding regime affected viral titers [ 30 , 31 ]. However, maintenance of bacterial microbiome commensals in the non-pathogenic commensal state requires active policing by basal host immunity [ 32 ].…”
Section: Discussionmentioning
confidence: 89%
“…In general, prevalent members of the natural virome should evolve towards lower pathogenicity in their habitual host lineages. Consistent with that expectation, a symbiotic Anopheles densovirus (studied for its potential use as a paratransgenesis tool) elicited low transcriptional response upon infection, and neither mosquito age at infection nor feeding regime affected viral titers [ 30 , 31 ]. However, maintenance of bacterial microbiome commensals in the non-pathogenic commensal state requires active policing by basal host immunity [ 32 ].…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies reported that AgDNV is venereally transmitted from infected males to the spermatheca of mated females (6). To test whether sexually-transmitted AgDNV can also lead to disseminated infection in mated females, we again allowed uninfected, virgin females to mate with either AgDNV- or PBS-injected males.…”
Section: Resultsmentioning
confidence: 99%
“…In its natural An. gambiae host, AgDNV can infect both sexes and all developmental stages, replicating particularly well in adults post-emergence (6, 7). Notably though, AgDNV is a benign virus that does not cause mortality or even a marked transcriptional response in its mosquito host (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Densoviruses (DNVs) persist as chronic infections in mosquito origin cells, and metagenomic techniques also confirm their presence in wild‐caught mosquitoes (O'Neill et al, ; Shi et al, ). In addition to this, DNVs also infect all developmental stages of mosquitoes which leads to larval death (Barik, Suzuki, & Rasgon, ; Barreau, Jousset, & Bergoin, ). Mosquito densoviruses (MDVs) have been identified in multiple mosquito species, such as Ae.…”
Section: Resultsmentioning
confidence: 99%